Ocular Pursuit Responses to Repeated, Single-Cycle Sinusoids Reveal Behavior Compatible With Predictive Pursuit - Barnes, G. R; Barnes, D. M; Chakraborti, S. R (Journal of neurophysiology, 2000)
Medical Research Council Human Movement and Balance Unit, Institute of Neurology, London WC1N 3BG, United Kingdom Barnes, G. R., D. M. Barnes, and S. R. Chakraborti. Ocular Pursuit Responses to Repeated, Single-Cycle Sinusoids Reveal Behavior Compatible With Predictive Pursuit. J. Neurophysiol. 84: 2340-2355, 2000. The link between anticipatory smooth eye movements and prediction in sinusoidal pursuit was investigated by presentation of series of identical, single-cycle, sinusoidal target motion stimuli. Stimuli occurred at randomized intervals (1.2-2.8 s) but were preceded by an audio warning cue 480 ms before each presentation. Cycle period ( T ) varied from 0.64 to 2.56 s and target displacement from 4 to 20° in separate series. For T    1.28 s, responses to the first stimulus of each series exhibited a time delay across the whole cycle (mean = 121 ms for T  = 0.8 s). But, in the second and subsequent (steady-state) presentations, anticipatory movements, proportional to target velocity, were made and time delay was significantly reduced (mean = 43 ms for T  = 0.8 s). Steady-state time delays were comparable to those evoked during continuous sinusoidal pursuit and less than pursuit reaction time. Even when subjects did not follow the target in the first presentation, they responded to the second presentation with reduced time delay. Throughout the experiments, three types of catch trial ( A-C ) were introduced. In A , the target failed to appear as expected after the warning cue. Anticipatory smooth movements were initiated, reaching a peak velocity proportional to prior target velocity around 200 ms after expected target onset. In B , the target stopped midway through the cycle. Even if the target remained on and was stationary, the eye movement continued to be driven away from the stationary target with a velocity similar to that of prior responses, reaching a peak velocity that was again proportional to expected target velocity after 205 ms. In C, the amplitude of the single sinusoid was unexpectedly increased or decreased. When it decreased, eye velocity throughout the first half-cycle of the response was close to that executed in response to prior stimuli of higher velocity and did not return to an appropriate level for 382-549 ms. Conversely, when amplitude increased, eye velocity remained inappropriately low for the first half-cycle. Results of A and C indicate that subjects are able to use velocity information stored from prior presentations to initiate an oculomotor drive that predominates over visual feedback for the first half-cycle. Results of B indicate that the second part of the cycle is also preprogrammed because it continued despite efforts to suppress it by fixation. The results suggest that initial retinal velocity error information can be sampled, stored, and subsequently replayed as a bi-directional anticipatory pattern of movement that reduces temporal delay and could account for predictive control during sinusoidal pursuit.